Spatial analysis to identify differentials in dental needs by area-based measures - Antunes JLF, Fraza˜o P, Narvai PC, Bispo CM, Pegoretti T. (Blackwell Synergy, 2002)
To examine the association between tooth decay and dental treatment needs in 5–12-year-old schoolchildren in Sa˜o Paulo with area-level indicators of social development.